Prevalence and Major Risk Factors for Atrial Fibrillation - D.M. Akpanova; A.T. Mussagaliyeva; S.F. Berkinbayev; D.A. Ospanova (Journal of Pharmacy and Nutrition Sciences, 2019)
This research paper studies prevalence and major risk factors for atrial fibrillation. This problem is very important and significant nowadays in the medicine. People are suffering a lot and is considered one of the major health problems. Atrial fibrillation (AF) is a heart rhythm disorder that increases the risk of stroke, disability, and mortality. The prevalence of AF in the adult population is on average 0.4–2%. According to the Global Burden of Disease (GBD) Study, about 33.5 million people in the world suffer from AF. The aim of our study was to study the prevalence of AF among the adult population of Almaty and Almaty region and the risk factors for the development of AF. Of the 1,575 respondents, 52 were found to have AF, which was 3.3%. The main risk factors for the development of AF / TP were age, diseases of the cardiovascular system, type 2 diabetes mellitus and overweight.